2007
DOI: 10.1056/nejmoa071255
|View full text |Cite|
|
Sign up to set email alerts
|

A Multicenter, Randomized, Controlled Trial of Dexamethasone for Bronchiolitis

Abstract: In infants with acute moderate-to-severe bronchiolitis who were treated in the emergency department, a single dose of 1 mg of oral dexamethasone per kilogram did not significantly alter the rate of hospital admission, the respiratory status after 4 hours of observation, or later outcomes. (ClinicalTrials.gov number, NCT00119002 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(133 citation statements)
references
References 35 publications
4
121
1
6
Order By: Relevance
“…However, a clinically important, significant effect has been documented for neither adrenaline nor beta-2-agonists 11,12 . Corticosteroids have not clearly been shown to be of significant benefit in improving the clinical status of patients with bronchiolitis.However, in some countries they are used routinely 13 . Antibiotic is commonly used in children with bronchiolitis, but should not be indicated unless bacterial infection is suggested [15][16][17][18] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a clinically important, significant effect has been documented for neither adrenaline nor beta-2-agonists 11,12 . Corticosteroids have not clearly been shown to be of significant benefit in improving the clinical status of patients with bronchiolitis.However, in some countries they are used routinely 13 . Antibiotic is commonly used in children with bronchiolitis, but should not be indicated unless bacterial infection is suggested [15][16][17][18] .…”
Section: Resultsmentioning
confidence: 99%
“…A multicenter trial from the Pediatric Emergency Care Applied Research Network, which enrolled 600 previously healthy infants with a first episode of bronchiolitis, showed that a single oral dose of dexamethasone resulted in no significant improvement compared with placebo in the rate of hospitalization or clinical scores 13 . Nebulized hypertonic saline has been associated with improvement in clinical score and duration of hospitalization in recent randomized trials though our patients did not receive it 14 .…”
Section: Resultsmentioning
confidence: 99%
“…5,17 The Pediatric Emergency Care Applied Research Network (PECARN) was established to overcome the barriers of conducting research pertaining to acutely ill and injured children during all phases of emergency care and has a history of successful completion of large multicenter clinical trials. [18][19][20][21][22][23][24][25] Due to the promising preclinical and phase II studies for the use of progesterone for adult TBI, PECARN investigators were funded to conduct feasibility planning for a clinical trial of progesterone and other promising agents for TBI in children. 26 In this article we report a prospective observational feasibility study of children with moderate-to-severe TBI presenting to 16 pediatric EDs across the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown no evidence of benefit for injectable systemic steroids. 29,30 Two randomised controlled trials showed no evidence of benefit for inhaled corticosteroids (ICS) in acute bronchiolitis. 31,32 Routine use of systemic or inhaled steroids in the management of bronchiolitis is therefore not indicated.…”
Section: Management Should Includementioning
confidence: 99%